Reproductive Responses, Metabolic Disorder, Ruminal Fermentation Characteristics, and Milk Production of Postpartum Holstein Cows Fed Steam Flaked of Corn and Barley Grains - N. Ahmadijoo; H. Mansoori-Yarahmadi; J. Fakhraei; M. Changizi (Faculty of Animal Science, Bogor Agricultural University, 2020)
This study evaluated the effects of steam flaked of corn and barley grains on the reproductive response, ruminal fermentation characteristics, metabolic disorder, and milk production of postpartum Holstein cows. A total of 40 postpartum Holstein dairy cows were divided into 4 groups (n=10) and fed 1) ground grains (control), 2) steam flacked corn+milled barley, 3) steam flacked barely+milled corn, and 4) steam flaked corn and barley. The animals were treated for 0-30, 30-60, 60-90, and 90-120 days post-calving. Milk yield and compositions, total conception rate, endometritis, pyometra, ruminal fermentation characteristics, ketosis, and acidosis were assessed. This study was conducted in a completely randomized design. The results showed that dietary inclusion of steam flaked grains improved milk yield and compositions during the experimental period compared to the control group (p<0.05), except for cows treated for 0-30d days post-calving. Cows fed steam flaked grains showed a lower occurrence of reproduction and metabolic disorders compared to the control group (p<0.01). Cows fed a combination of steam flaked grains showed better pregnancy rates in the first 100 days and open days of postpartum cows compared to cows in control and a single form of steam flaked barley or corn (p<0.05). Total VFA, acetate, propionate, butyrate, and valerate were higher in cows fed steam flaked compared to the control group (p<0.05). Feeding steam flaked grains is advised for improving reproductive performance, milk variables, and rumen fermentation profiles in dairy cows.